Preliminary Study as Temperature Sensor of Nanosilica Based on Coastal and River Sand - Meiliyadi, Lalu Ahmad Didik; Wahyudi, Muh.; Arizona, Kurniawan (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
The synthesis of nano-silica gel based on magnetic minerals from the coastal sand and river sand of Lombok Island has been carried out. The synthesis method used is sol-gel with HCl acid and NH4OH base. The results showed that nano-silica based on coastal sand has a greater silica content than nanosilica based on river sand. The morphology of nanosilica based on coastal is granular with a smaller grain size of nanosilica based on coastal sand compared to nanosilica based on river sand. To a temperature sensor, nano-silica based on coastal sand has a larger coefficient when compared to nanosilica based on river sand. This indicates that nano-silica based on coastal sand has better physical properties as a temperature sensor than nanosilica based on river sand.